Dienoraštis, papildantis pasitraukimo iš Lietuvos 1944 metais pasakojimus - Vanagaitė, Gitana (Colloquia, 2024)
Vytautas Osvaldas Virkau. Dienoraštis, 1944–1952, sudarytoja Dalia Kuizinienė. Vilnius: Versus, 2023, 264 p., ISBN 978-9955-829-49-2